Impact of Gender and Age on Clinical and Medical Features of Rheumatoid Arthritis in Tripoli, Libya - El Magrahi, Hamida; Maryam Belgasem,; Shahed Aldeeb,; Ahlam Abdullah, (AlQalam Journal of Medical and Applied Sciences, 2026)
Rheumatic disorders, which exhibit notable age- and gender-related demographic trends, are characterized by inflammation and discomfort in the joints and connective tissues. This study aimed to evaluate the demographic characteristics and inflammatory biomarker profiles of patients with rheumatic illnesses and to examine the relationship between these characteristics and age and gender. Between September and November of 2025, 70 patients with rheumatic diagnoses from various clinics in Tripoli, Libya, participated in the study. Every patient underwent laboratory testing. The Alshark Laboratories was the site of this investigation. All participants were asked to complete the questionnaire in order to gather information on their age, sex, and health. Females constituted the majority of the study population (61.4%), while males accounted for 38.6%. Adults (>16 years) represented 60.0% of participants, and children (≤16 years) accounted for 40.0%. A statistically significant association was observed between age group and gender distribution (P= 0.009), with males predominating among children and females predominating among adults. Female patients exhibited significantly higher Antistreptolysin O titer (ASO) levels compared with males (median: 316.0 vs. 189.0 IU/mL; P = 0.047). Erythrocyte Sedimentation Rate (ESR) values also differed significantly between genders (P = 0.048), whereas no significant gender-based differences were observed in C-Reactive Protein (CRP) and Rheumatoid Factor (RhF). When comparing age groups, children showed higher ASO levels than adults; however, this difference was not statistically significant (P = 0.060). No significant differences were found between children and adults for CRP, ESR, and RhF. Spearman’s correlation analysis revealed a significant negative correlation between age and ASO levels (IQR = −0.244, P = 0.042) and a weak but significant positive correlation between age and ESR (IQR = 0.264, P = 0.027). No significant correlations were observed between age and CRP and RhF. The results show significant variations in the distribution of rheumatic illness patients by age and gender, as well as in several inflammatory biomarkers, including ASO and ESR. These findings demonstrate how crucial it is to take demographics into account when analyzing inflammatory marker profiles in rheumatic illness patients.